MANAJEMEN KURIKULUM 2013 OLEH KEPALA SEKOLAH - Diana Sari (UNIVERSITAS BENGKULU, 2015)
The general purpose of the research was to describe curriculum 2013 management by principle in public Senior High School Number 1 Seluma Regency. The results of the researchwas: (1) planning of curriculum 2013 by principle was done well. (2) organizing the implementation of curriculum 2013 by the principle senior teacher who understand more about curriculum 2013. (3) principle role in succesing the implementation of curriculum 2013 was very vital, he was always held a supervision to his teachers, monitoring and evaluating the progress. (4)the principle in solved the problems faced in implementing curriculum 2013 was downloaded teachers guide and student guide book trought internet and coordinating with vice headmaster and curriculum development team.Keywords: Management, curriculum 2013, principles